Quality Teaching Practices: Implementing Instruction - صالحــــي, أحلام (Revues faculté des lettres et des langues; No 13 (2013): مجلة كلية الآداب واللغات, 2014)
معظم الدراسات تركز على الصفات الشخصية للأستاذ والسلوكيات الاجتماعية والتنظيمية التي تحيط عملية التدريس. مما لا شك فيه إنّ استعداد الأستاذ  وعلاقته الوثيقة مع الطلاب، وأساليبه في  إدارة الصف كلها عناصر تؤدي إلى نجاح عملية التدريس. لكن عندما يتعلق الأمر بتقييم جودة التدريس، لا يوجد شيء أكثر أهمية من التدريس في حد ذاته. فيما يتعلق بهذا الغرض، يقدم المقال لمحة عامة عن جودة التدريس من حيث الممارسة التعليمية من خلال التركيز على البحوث التي تناولت العناصر المهمة في التدريس   Most of studies focus on the teacher’s personal qualities and social and organizational behaviors that surround the teaching process. Undoubtedly, a teacher’s preparation, relationships with students, and classroom management techniques are inextricably linked with classroom success. When it comes to assessing quality teaching effectiveness, however, there is nothing more important to consider than the actual act of teaching. In relation to this purpose, the paper provides an overview of the effective     quality teaching in terms of instructional practice by focusing on research-based elements of teaching.